Rayleigh-taylor instability experiments with precise and arbitrary control of the initial interface shape. - Huang, Zhibin.; De Luca, Antonio.; Atherton, Timothy J.; Bird, Matthew.; Rosenblatt, Charles.; Carlès, Pierre. (Tufts University. Tisch Library., 2017)
In a Rayleigh-Taylor instability a dense fluid sits metastably atop a less dense fluid, a configuration that can be stabilized using a magnetic field gradient when one fluid is highly paramagnetic. On switching off the magnetic field, the instability occurs as the dense fluid falls under gravity. By affixing appropriately shaped magnetically permeable wires to the outside of the cell, one may impose arbitrarily chosen and well-controlled initial perturbations on the interface. This technique is used to examine both the linear and nonlinear growth regimes for which the perturbation amplitudes, growth rates, and nonlinear growth coefficients are obtained.